Preoperative education prior to elective knee arthroplasty surgery does not change patient outcomes. (4th January 2017) - Moulton, Lawrence Stephen; Evans, Peter A.; Starks, Ian; Smith, Tony
Abstract: Enhanced recovery programmes have improved outcomes following elective arthroplasty surgery. There are few studies assessing the role of patient education. In our enhanced recovery programme, all patients are offered the chance to attend a preoperative education class. Not all patients attend, enabling a comparison of outcomes. We have published data demonstrating that patients undergoing hip arthroplasty have improved outcomes. In the present article, we present data for total knee arthroplasty. Using a prospectively collected database, we identified all patients undergoing elective primary total knee arthroplasty. Data were assessed to look at patient outcomes. This was analysed using non‐parametric tests. Between April 2009 and March 2013, 563 patients underwent elective total knee replacement. A total of 503 attended the class and 60 did not. Patients attending had a reduced length of stay when compared with the non‐attenders but this did not reach statistical significance (4.13 days versus 4.57 days; p  = 0.118). The spread of length of stay was slightly larger in the group that attended. Our analysis demonstrated that, for these patients, there is no statistically significant difference in length of stay or outcome scores. Therefore, in tougher economic times it may be prudent to focus preoperative education on total hip arthroplasty patients if resources are limited.